Assessment of Finger and Palmar Dermatoglyphics in Thalassemia Patients in Gujarat: A Search for Diagnostic Traits - Rawal, Jitendra; Patel, Maulik; Jethva, Nishita; Patel, Dhaval (Journal of Neonatal Surgery, 2025)
Background: Thalassemia is a common hereditary blood disorder with a high prevalence in India. Dermatoglyphics, the study of epidermal ridge patterns, has shown potential as a noninvasive indicator of various genetic conditions. This study aims to evaluate finger and palmar dermatoglyphic patterns in patients with thalassemia and assess their potential diagnostic significance. Objectives: To analyze finger and palmar dermatoglyphic features in thalassemia patients and identify whether specific dermatoglyphic traits are consistently associated with the disease. Materials and Methods: This observational, cross-sectional study included 60 clinically diagnosed thalassemia patients attending the Thalassemia OPD at Civil Hospital, Ahmedabad, during February and March 2013. Detailed clinical data were recorded. Finger and palmar prints were obtained using the ink method described by Cummins and Midlo. Total finger ridge count (TFRC), absolute finger ridge count (AFRC), ‘atd’ angle, ‘ab’ and ‘cd’ ridge counts, and fingerprint patterns were analyzed. Results: Among 600 fingertip patterns studied, ulnar loops were the most frequent (56.5%), followed by whorls (32.2%), arches (8.7%), and radial loops (2.6%). The mean TFRC and AFRC were 117.2 and 148.6, respectively. The mean 'atd' angle was 42.4° in the right hand and 44.3° in the left. Increased ‘ab’ and ‘cd’ ridge counts were also noted. These findings showed a predominance of loop patterns and increased ridge parameters, in line with previous literature. Conclusion: Dermatoglyphic traits such as increased ulnar loops, ridge counts, and wider 'atd' angles are more common in thalassemia patients. These features may serve as useful adjunct markers for screening and early identification, especially in resource-limited settings.